Transcoding-Enabled Edge Caching and Delivery for Tile-Based Adaptive 360-Degree Video Streaming - Lu, Qiaoyu; Li, Chenglin; Zou, Junni; Tang, Kexin; Wang, Qi; Xiong, Hongkai (Visual communications and image processing (Online), 2019)
The high-definition and panorama characteristics of 360-degree video make its transmission in existing networks more challenging. To alleviate this problem, this paper leverages transcoding-enabled edge caching in tile-granularity and makes joint caching, transcoding and delivery decisions among multiple edge servers for adaptive 360-degree video streaming. We formulate the joint caching, transcoding and delivery decision-making problem as a multivariate nonlinear integer programming problem, aiming at minimizing the aggregate network operational cost and balancing the server load, subject to storage and computation capacity constraints of the edge servers. Through decomposition and relaxation approach, the original intractable optimization problem is solved by an effective iterative algorithm. Finally, simulation results show that the proposed iterative algorithm outperforms the existing schemes in terms of resource utilization, cost reduction and server coordination.